First On-line beta-NMR on oriented nuclei: magnetic dipole moments of the (nup(1/2))(-1) 1/2(-) ground state in 67Ni and (pip(3/2))(+1) 3/2(-) ground state in 69Cu - Rikovska, J; Giles, T; Stone, N; van Esbroeck K; White, G; Wohr, A; Veskovic, M; Towner, I; Mantica, P; Prisciandaro, J; Morrissey, D; Fedoseyev, V; et al. (2000)
The first fully on-line use of the angular distribution of beta emission in detection of NMR of nuclei oriented at low temperatures is reported. The magnetic moments of the single valence particle, intermediate mass, isotopes 67Ni(nup(-1)(1/2);1/2(-)) and 69Cu(pip(1)(3/2);3/2(-)) are measured to be +0.601(5) andmgr;(N) and +2.84(1) andmgr;(N), respectively, revealing only a small deviation from the neutron p(1/2) single-particle value in the former and a large deviation from the proton p(3/2) single-particle value in the latter. Quantitative interpretation is given in terms of core polarization and meson-exchange currents.